Comparison of Uplift Pressure and Hydraulic Gradient in Three Types of Dams: Concrete Gravity Dams, Homogeneous and Heterogeneous Earth-Filled Dams - Farzin Salmasi; John Abraham (Innovations in Science and Technology Vol. 3, 2022)
Dams are among the world’s oldest hydro-engineering structures. They are constructed to control flooding and safeguard land, property, people and livestock. Knowledge of uplift pressure and hydraulic gradient are essential for dam designers because they impact the stability of the dam. Dam stability refers to dam sliding, overturning and maximum stresses (tension or compression) that are exerted on the dam foundation. This study focuses on the hydraulic gradient and uplift pressure in three types of dams, i.e., homogeneous earth dams, heterogeneous earth dams, and concrete gravity dams. Seepage, hydraulic gradient and uplift pressure were computed by numerical simulation, using the finite element method (FEM). The dam geometry, material, the computational mesh, and boundary conditions (BCs) are all input into the FEM. Results showed that the hydraulic gradient for two types of dams, i.e., the concrete gravity and the homogeneous earth dam, were similar and were less than 0.5. But the hydraulic gradient exceeded 2.5 at the beginning and ending of the clay core heterogeneous earth dam. Implementation of filter material in such zones will be necessary to prevent the dam foundation from piping/undermining phenomenon. The uplift pressures for the two earth dams exceeded that of the concrete gravity dam. It is believed that uplift pressure for earth dams is not dangerous because of the large width of earth dams prevents them from overturning.